Roles of Vision Rehabilitation Therapists in the 21st Century. (May 2020) - Connors, Elyse; Lee, Helen
Introduction: Vision rehabilitation therapists (VRTs) carry out many specific job tasks. This study seeks to better understand the VRT profession by organizing many tasks into a few specific roles in which VRT practitioners are involved. Methods: Using the results of the 2017 online survey, a principle component analysis was carried out to extract clusters of specific job tasks. The reliability of the resulting job role constructs was assessed using Cronbach's alpha. Results from this analysis are compared to a similar analysis of VRT job roles conducted 28 years ago. Results: Four job roles are extracted from the survey's frequency data: (1) teaching activities, (2) case management, (3) technology, and (4) low vision and assessment. Seventy specific job tasks are retained under the four roles. Discussion: Extracted job roles of teaching and case management are similar to Leja's (1990) findings, indicating that these roles remain important aspects of the VRT job. Two new roles have emerged since Leja's examination, and they are related to technology and low vision and assessment. The advancement, availability, and affordability of technologies and low vision interventions has increased the need for teaching the use of access technologies across the daily living spectrum. The availability of low vision devices has expanded the role of the VRT in the provision of functional low vision assessments, strategies for reading and daily tasks, appropriate use of optical and nonoptical aids, and environmental assessment for safety and optimal visual performance. Implications for practitioners: VRT survey participants are performing additional job roles in technology and low vision and assessment. This presents challenges related to resources and training for practitioners who already provide instruction across a broad set of skill domains. Issues include access to new technologies, adequate time to learn new devices and software, and standardized assessment tools.